(untitled) (International journal of artificial intelligence, 2026)
The article analyzes the problem of developing the reflexive skills of doctors in modern medical education, its theoretical and methodological foundations, and the mechanisms of practical application. The study, based on the results of experimental work conducted in medical higher educational institutions of Andijan, Bukhara, and Fergana, reveals the influence of the reflexive approach on the quality of clinical decision-making, patient safety, empathy, and professional stability. The author's methodology was developed based on the integration of a reflective diary, portfolio, simulation, debriefing, and mentoring, the effectiveness of which is substantiated by empirical and statistical analysis.